Association Between Fetal Congenital Heart Defects and Maternal Risk of Hypertensive Disorders of Pregnancy in the Same Pregnancy and Across Pregnancies. Issue 1 (4th July 2017) - Boyd, Heather Allison; Basit, Saima; Behrens, Ida; Leirgul, Elisabeth; Bundgaard, Henning; Wohlfahrt, Jan; Melbye, Mads; Øyen, Nina
Abstract : Background: Both pregnant women carrying fetuses with heart defects and women with hypertensive disorders of pregnancy often exhibit angiogenic imbalances, suggesting that the same mechanisms are involved in the pathogenesis of the former and the pathophysiology of the latter. We conducted a register-based cohort study to determine whether offspring congenital heart defects are associated with an increased risk of hypertensive disorders of pregnancy and whether the mechanisms driving any association are primarily maternal or fetal. Methods: Among singleton pregnancies without chromosomal abnormalities lasting ≥20 weeks in Denmark from 1978 to 2011 (n= 1 972 857), we identified pregnancies complicated by offspring congenital heart defects or early preterm preeclampsia, late preterm preeclampsia, term preeclampsia, and gestational hypertension. We used polytomous logistic regression to estimate odds ratios (ORs) for associations between offspring congenital heart defects and maternal hypertensive disorders of pregnancy overall and for specific heart defects. Results: Offspring congenital heart defects were strongly associated with early preterm preeclampsia (OR, 7.00; 95% confidence interval [CI], 6.11–8.03) and late preterm preeclampsia (OR, 2.82; 95% CI, 2.38–3.34) in the same pregnancy and weakly associated with term preeclampsia (OR, 1.16; 95% CI, 1.06–1.27), but they were not associated with gestational hypertension (OR, 1.07; 95% CI, 0.92–1.25). Association strengths were consistent across heart defect types. Offspring congenital heart defects in a previous pregnancy were also strongly associated with preterm preeclampsia in subsequent pregnancies (early preterm preeclampsia: OR, 2.37; 95% CI, 1.68–3.34; late preterm preeclampsia: OR, 2.04; 95% CI, 1.52–2.75) but were only modestly associated with term preeclampsia and not associated with gestational hypertension. Similarly, preterm preeclampsia in a previous pregnancy, but not term preeclampsia or gestational hypertension, was associated with offspring congenital heart defects in later pregnancies (early preterm preeclampsia: OR, 7.91; 95% CI, 6.06–10.3; late preterm preeclampsia: OR, 2.83; 95% CI, 2.11–3.79; term preeclampsia: OR, 0.98; 95% CI, 0.88–1.10; gestational hypertension: OR, 1.13; 95% CI, 0.92–1.38). Conclusions: Linked pathophysiological mechanisms may be involved in some congenital heart defects and preterm preeclampsia. The strong associations across pregnancies support a predominantly maternal origin of effect. Abstract : Supplemental Digital Content is available in the text.